2019
DOI: 10.31248/jasvm2018.110
|View full text |Cite
|
Sign up to set email alerts
|

Effect of graded levels of Moringa oleifera leaf meal on performance and serum biochemical parameters of broiler chickens

Abstract: Ninety-six (96) CHI broiler chickens aged 4 weeks were used to determine the effect of Moringa oleifera leaf meal (MOLM) on growth performance and serum biochemical parameters. The 96 broiler chickens were randomly allocated to 4 treatment groups, identified as T1, T2, T3 and T4. Each treatment group consisted of 24 birds replicated 3 times with 8 birds per replicate in a Completely Randomized Design (CRD) with four levels of Moringa leaf meal as treatments. The levels of Moringa leaf meal were 0.00%, 6.00%, 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 5 publications
4
3
0
Order By: Relevance
“…The present findings are in related with Kout et al, (2015) who reported that best feed conversion ratio in birds fed on 0.2% MOLM. The result was line with finding of Egu, (2019) who observed that the MOLM showing best feed conversion ratio as compared to without MOLM diet. Onunkwo and George et al, (2015) reported significant decrease in the feed conversion ratio of the birds fed MOLM levels 0.0%, 5.0%, 7.5% and 10% based diets.…”
Section: Feed Conversion Ratiosupporting
confidence: 91%
“…The present findings are in related with Kout et al, (2015) who reported that best feed conversion ratio in birds fed on 0.2% MOLM. The result was line with finding of Egu, (2019) who observed that the MOLM showing best feed conversion ratio as compared to without MOLM diet. Onunkwo and George et al, (2015) reported significant decrease in the feed conversion ratio of the birds fed MOLM levels 0.0%, 5.0%, 7.5% and 10% based diets.…”
Section: Feed Conversion Ratiosupporting
confidence: 91%
“…Body weight gain (BWG) was highest (P<0.01) in broilers fed diet supplemented with 1.5% MOLM with multi enzyme @ 50g/100 kg feed at starter and finisher phase (Table 2). This result is akin to Egu (2019) who found that the inclusion of MOLM in diet of broilers significantly (P<0.05) enhanced the weight gain at 3 and 6 week age. Swian et al, 2014 observed significantly (P<0.05) higher body weight gain in broilers fed with enzyme supplemented ration than control during starter (0-21 days) and finisher (22-42 days) phase.…”
Section: Growth Performancesupporting
confidence: 72%
“…The inclusion of 7.5% M. oleifera leaf meal in broiler feeds had not affected weight gain, feed intake and feed conversion ratio, but above this level feed intake decreased (Gakuya et al, 2014). Moringa oleifera leaf meal at 8% dietary level improved weight gain, but no effects were shown regarding feed intake and feed conversion ratio (Egu, 2019), while the inclusion of 7.5 and 10% in diets for one-week old chicken decreased growth rate (Limcangco-Lopez et al, 1989). Several previous studies agreed that the use of M. oleifera leaf meal up to a level of 10% had no negative effect on the performance of broiler chicken, while levels above 10% showed negative effects on performance (Kakengi et al, 2007;Olugbemi et al, 2010;Onu & Aniebo, 2011;Abou-Elezz et al, 2011;Zanu at al., 2012;Gadzirayi et al, 2012;Banjo, 2012).…”
Section: Growth Performancementioning
confidence: 83%
“…The addition of 0.2, 0.4 and 0.6% M. oleifera meal leaves reduced aspartic transaminase (AST) activity insignificantly, but there was a significant decrease in alanine transaminase (ALT) by the addition of 0.4% M. oleifera, which may reflect normal liver function of the birds fed diets containing M. oleifera leaves meal (Makanjuola et al, 2014;Akinola & Ovotu, 2018). Egu (2019) indicated that urea, cholesterol, glucose, calcium and alkaline phosphatase values were reduced in group fed 10% M. oleifera leaf meal comparing to control birds.…”
Section: Biochemical Parametersmentioning
confidence: 99%